2016
DOI: 10.1016/j.redox.2016.09.010
|View full text |Cite
|
Sign up to set email alerts
|

Glutathione maintenance mitigates age-related susceptibility to redox cycling agents

Abstract: Isolated hepatocytes from young (4–6 mo) and old (24–26 mo) F344 rats were exposed to increasing concentrations of menadione, a vitamin K derivative and redox cycling agent, to determine whether the age-related decline in Nrf2-mediated detoxification defenses resulted in heightened susceptibility to xenobiotic insult. An LC50 for each age group was established, which showed that aging resulted in a nearly 2-fold increase in susceptibility to menadione (LC50 for young: 405 μM; LC50 for old: 275 μM). Examination… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 101 publications
0
16
0
Order By: Relevance
“…5 j). This metabolite decreased across ages in Ctrl mice, but did not change across age in AD mice, suggesting that glutathione is specifically related to ARCD 46 . In addition, all of the changed metabolites are implicated in protein synthesis and oxidative stress, both of which have been implicated in AD pathology 47 , 48 .…”
Section: Resultsmentioning
confidence: 84%
“…5 j). This metabolite decreased across ages in Ctrl mice, but did not change across age in AD mice, suggesting that glutathione is specifically related to ARCD 46 . In addition, all of the changed metabolites are implicated in protein synthesis and oxidative stress, both of which have been implicated in AD pathology 47 , 48 .…”
Section: Resultsmentioning
confidence: 84%
“…In a prior study, we established that hepatocytes from old rats were nearly 50% more susceptible to menadione (LC 50 young: 405 μM; old: 275 μM) with significant differences in GSH loss and increased markers of lipid peroxidation within minutes [25]. To determine whether the enhanced toxicity from menadione insult was mediated at least in part through mitochondrial dysfunction, we treated hepatocytes isolated from young and old F344 rats with 300 μM menadione (the ∼LC 50 for old) and assayed mGSH levels over a 20 min time-course.…”
Section: Resultsmentioning
confidence: 99%
“…Menadione is a potent redox cycling compound that generates a strong, persistent oxidative stress via the initial generation of superoxide followed by its dismutation into more deleterious ROS/RNS [26,54]. We have previously demonstrated that the age-related increase in vulnerability to acute challenge with this compound is GSH-dependent [25]. Additionally, menadione treatment in isolated mitochondria was previously demonstrated to deplete GSH and inhibit Complex I activity [27,55].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A major hallmark of aging, and a key driver for the onset of age-related pathophysiologies is the disruption of cellular redox homeostatic mechanisms that protect against environmental factors, such as oxidative, pathological, and toxicological insults [ 25 ]. During aging, weakened antioxidant defenses allow the accumulation of toxic reactive oxygen species that contribute to aging and to the onset of multiple diseases [ 9 ].…”
Section: Discussionmentioning
confidence: 99%